Nutritional status in children with esophageal stenosis and dysphagia associated with caustic ingestion - Carmen A. Sánchez-Ramírez; Alfredo Larrosa-Haro; Edgar M. Vásquez Garibay; Ana K. Rodríguez-Anguiano; María E. Cámara-López (Nutrición Hospitalaria)
Introduction: Caustic ingestion (CI) in children and adolescents may lead to esophageal burns, esophageal stenosis and secondary dysphagia. These complications may limit the normal feeding process leading to malnutrition and growth impairment. Aims: Our aim was to evaluate the nutritional status and its association with dysphagia and esophageal stenosis in children with CI. Methods: Sixty-two patients with caustic ingestion treated at a pediatric referral hospital were included in this cross-sectional study. Independent variables were dysphagia/normal swallowing and esophageal stenosis/normal barium-swallow. The dependent variables were growth and nutritional status evaluated by anthropometry. Analysis: χ² test, OR, 95% CI, kappa test and Student's t-test. Results: The average age at the time of CI was 39.7 months; 38.7% of the patients were girls. Endoscopy performed upon admission revealed erosive esophagitis (II-b, III-a, and III-b) in 46 (77.8%) of the patients, dysphagia in twenty-four (38.7%) and esophageal stenosis in forty (64.5%). Both complications occurred simultaneously in 20 children (32.3%, kappa = 0.3, p = 0.014). The z-score of height-for-age was below -2 SD in five children (8.1%). The z score of body mass index (BMI) was < -2 SD in three children (4.8%) and it was above +1 SD in 24.2%. The z-score means of the arm anthropometric indicators of fat stores and muscle mass in both the dysphagia and esophageal stenosis groups were located in the negative area of the z-score curve and their values differed significantly from the z-scores of the non-dysphagia and non-stenosis groups. Conclusions: The proportion of erosive esophagitis, esophageal stenosis and dysphagia was high. Children with dysphagia and/or esophageal stenosis associated with CI had lower fat stores and muscle mass than the cases without esophageal complications.